Linezolid susceptibility in MRSA isolates: insights into resistance and concordance in phenotypic detection methods - Bawankar, Neha Sunil; Agrawal, Gopal N.; Zodpey , Sunanda S. (International Journal of Research in Medical Sciences, 2024)
Background: Methicillin-resistant staphylococcus aureus (MRSA) poses persistent threat, affecting both healthcare environment and communities, with substantial impact on infection rates, morbidity, mortality, and healthcare costs. Vancomycin, a longstanding cornerstone in MRSA treatment, but with the emergence of vancomycin resistant MRSA (VRSA), necessitating alternative antimicrobial solutions. Linezolid, stands out as a promising candidate. It has unique advantages such as an absence of renal toxicity and improved lung parenchymal diffusion compared to vancomycin, making it an appealing choice, especially for healthcare-acquired pneumonia by MRSA. Methods: This cross-sectional study investigated linezolid susceptibility in 158 MRSA isolates using both disk diffusion and agar dilution method. Results: Results indicated that the majority of isolates exhibited linezolid susceptibility, with 53.16% showing a minimum inhibitory concentration (MIC) of ≤2 µg/ml. However, two MRSA isolates, constituting 1.27% of the sample, displayed a MIC of 8 µg/ml, named them as a linezolid-resistant MRSA (LRSA). These findings align with previous research, mirroring resistance rates observed in different regions. Notably, vigilance against linezolid resistance is crucial, particularly due to its status as a last-resort MRSA treatment. Conclusions: Remarkably, a 100% concordance was found between the disk diffusion and MIC methods for detecting linezolid resistance in MRSA, suggesting that the disk diffusion method may be practical choice for laboratories with heavy workloads. However, adherence to CLSI guidelines is essential, and cases of resistance by disk diffusion should be confirmed using MIC methods. Emergence of linezolid-resistant MRSA is a worrisome development, necessitating ongoing surveillance and vigilance.